Sosialisasi Terkait Bullying Pada Siswa SDN 06 Sasak Ranah Pasisie Jorong Padang Jaya Kecamatan Sasak Ranah Pasisie Kabupaten Pasaman Barat - Hambali; Azahra, Nadya; Batubara, Nurul Hamdiah; Liswandari, Riva; Walhidayatul (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
In the educational environment, bullying violence often occurs and can have a negative impact on both the perpetrator and the victim. As a result, such actions must be taken seriously as they can hinder a student's future growth. Socialization activities related to bullying aim to increase knowledge about bullying and good behavior towards other people. The lecture method is used to provide this socialization material, which is packaged attractively with a PowerPoint display that is not boring. Many elementary school students learn about bullying during the question and answer session before the material. After the material is given, there is a quiz given. Many students were eager to answer them, which shows that they have understood the material well. After this socialization ended, students had an increased understanding of bullying